Prenatal risk factors for selected congenital anomalies development: A case-control pilot study in postpartum women from Argentina - Colussi, Carlina Leila (2023)
Introduction: Congenital anomalies (CAs) are abnormalities in intrauterine development and are one of the main causes of burden disease, especially in low and middle-income countries. Many environmental and maternal risk factors could lead to these pathologies. The aim of this study was to identify different types of CAs, determine their frequency and identify their possible association with maternal sociodemographic and lifestyle risk factors among patients from Santa Fe Province, Argentina. Material and methods: An observational cases and control pilot study was conducted in 2018 and 2019 on 280 postpartum mothers of newborn babies with any CA (cases, n = 64) and without a CA (controls, n = 216) attending public hospitals. A face-to-face questionnaire was completed, and clinical histories were required to obtain information on maternal sociodemographic factors, gynecological events, health state, lifestyle habits and child diagnoses. Results: Polymalphormations and neural tube defects were the most frequent CA observed. Differences between cases and control groups, as well as between places of residence, were given by gestational age, type of delivery and newborn birth weight, all of which are preventable variables. A slight association between maternal diabetes and the occurrence of cases was found. Discussion: Maternal place of origin is a factor of inequity in terms of gynecology variables which describes a deeper background in sanitary reality from Santa Fe Province that would have a large impact on future adults born preterm. The results highlight the necessity of generating both sanitary tools for maternal-child health policies and environmental evaluations, which remains a permanent challenge of the Argentine public health system.